(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Vaqf Book:1 The validity and invalidity of endowment actions, the establishment of endowments by religious scholars, the endowment of broad portions by affluent scholars, the beneficiary of endowment, the pros and cons of endowment (those who have stipulated conditions for the benefits and advantages of endowments), advocacy and witnessing in endowment matters, the granting of a thing endowed to an individual (given into possession) and the explanations of the rulings of other related issues are explained in this section, which consists of 9 chapters.